An appointment with Somerset Maugham : and other literary encounters - Costa, Richard Hauer (Texas A & M University Press, 1994)
""Now, just ask yourself," Maugham said without the least suggestion of a stutter, "wouldn't it be a dreadful world if pleasure ruled?" But pleasure has ruled Richard Costa's world - the pleasure of books and their writers. In this charming and insightful reminiscence, he introduces readers to a host of literary lives that have touched him: Somerset Maugham, H.G. Wells, Malcolm Lowry, Conrad Aiken, Edmund Wilson, Kingsley Amis, Dorothy Parker, Edith Wharton, and others." "The journey of the mind and heart Costa traces has some illustrious guides. Reading and re-reading the works of memorable writers of our time, interviewing them, and writing about them, he has woven literature into his life in a way that provides illumination and just plain interest for those who read the story here. In his intellectual and literary chronicle, readers will find much humor, much memory, and much food for thought."--Jacket
Keywords: Maugham, W. Somerset -- (William Somerset), -- 1874-1965 -- Critique et interprétation.; English literature -- 20th century -- History and criticism.; American literature -- 20th century -- History and criticism.; Littérature anglaise -- 20e siècle -- Histoire et critique.; Littérature américaine -- 20e siècle -- Histoire et critique.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; American literature; English literature; 1900-1999; Criticism, interpretation, etc.